Analisis Kualitas Laba Perusahaan Sebelum dan Selama Pandemi Covid-19 pada Perusahaan yang Terdampak Besar Pandemi Covid-19 - Sela Mandiri; Nurzi Sebrina (Universitas Negeri Padang, 2023)
This study is aims to compare the earnings quality before and during the Covid-19 pandemic. The population is all companies were most affected by the Covid-19 pandemic pandemic, namely the accommodation and restaurant, transportation, and trade sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020. Sampling was carried out by purposive sampling which resulted in 73 companies with 4 years of observation (2017-2020).The type of data is secondary data obtained form of financial statement. Analysis of the data used is multiple regression analysis. The results of the study show that firstly, there are differences in the quality of the accruals of the sample companies before and during the covid-19 pandemic. secondly, there are differences in earnings persistence in sample companies before and during the Covid-19 pandemic which is supported by a decrease in earnings persistence, where the condition of profit persistence in sample companies before the Covid-19 pandemic is better and more stable than during the Covid-19 pandemic. The three value relevance comparisons seen from the Adjusted R2 value show a decrease from before the pandemic to during the Covid-19 pandemic.